K-ras mutation predictive significance in platinum based chemotherapeutic protocols in patients with advanced non-small cell lung cancer - Cvetković Gordana; Plavec Goran; Tomić Ilija; Ilić Vesna; Magić Zvonko; Tatomirović Željka; Novković Dobrivoje; Milić Rade; Karličić Vukojica (Vojnosanitetski Pregled)
Beckground/Aim. K-ras oncogene is mutated in about 20% of lung cancer. The purpose of this study was to investigate the predictive significance for therapeutic response of K-ras mutations in advanced non-small cell lung cancer (NSCLC) patients. Methods. Bronchial aspirate samples were assessed prior to platinum-based chemotherapy start in 39 patients with stage IIIb or IV NSCLC. K-ras mutations at codons 12 and 13 were analyzed by single strand conformation polymorphisam (SSCP) and allele specific oligonucleozide hybridisation of polymerase chain reaction (PCR) of the patient's DNA present in bronchial aspirate. After two cycles of chemotherapy the patients were subjected to response evaluation. Results. Of 39 patients 10 (25.5%) demonstrated K-ras mutations, while 29 (74.4%) patients had not. There were no significant differences between these two groups of patients with respect to baseline patient characteristics. Partial response to the therapy had 16 (41%), no changes 14 (36%), and progressive disease 9 (23%) patients. There was a tendency to higher response rate for patients without K-ras mutations versus those with mutations, but not statistically significant (p = 0.14). Conclusion. There was no significant predictive value for therapeutic response of K-ras mutations for advanced non-small cell lung cancer.